Tailoring the mechanical properties of Ti6Al4V diamond metal lattice structures through a novel node-compensation technique targeting cortical bone - Shivakumar N; T Ramesh; Muthukumaran S (Materials Research Express)
This study introduces a novel node compensation (NC) technique for Ti6Al4V-based diamond metal lattice structures (MLSs). This approach reduces the stress concentration at strut junctions while enhancing the energy absorption capacity of the MLS. Node compensation involves removing one spherical node from a representative volume element (RVE) and compensating by increasing the diameters of the remaining nodes. This adjustment improves porosity while mitigating stress concentration factors. The NC structure and two purely strut-based designs (D1 and D2) with strut diameters of 500 μm and 575 μm, respectively, were modelled in SolidWorks and fabricated via the direct metal laser sintering (DMLS) technique. The strut and node dimensions were validated through micro-CT imaging. The scanning electron microscopy (SEM), electron backscatter diffraction (EBSD) and x-ray diffraction (XRD) were used to analyse the phase composition of Ti6Al4V. Quasistatic compression tests at a loading rate of 0.5 mm min ^−1 , combined with digital image correlation (DIC), revealed that the NC structure exhibited an extended plateau stress region in the 100–150 MPa range with more uniform deformation with less stress undulation than D1 and D2. D1 and D2 showed earlier densification than NC. The NC demonstrated a yield strength, ultimate strength, and quasielastic gradient (elastic modulus) of approximately 150 MPa and 200 MPa, 3.572 GPa, respectively, aligning with the mechanical properties of cortical bone.